Mitigation of osmotic stress by Serratia nematodiphila in tomato seedlings (Research, Society and Development, 2020)
Agriculture is the main economic activity responsible for the highest rates of water consumption worldwide. Understanding strategies that combine decreasing the amount of water available and reducing the addition of chemical fertilizers is a major challenge today. Within this context, the work aimed to evaluate the efficiency in promoting growth in tomato seedlings, inoculated with Serratia nematodiphila, submitted to different water deficit conditions. The methodology consisted of using tomato seeds cv. Santa Clara Miss Brasil previously disinfected and inoculated with the Serratia nematodiphila bacterium. The experimental design was completely randomized in the factorial scheme 2 (with bacteria and without bacteria) x 3 (irrigation levels: 100%, 50% and 25% water), making a total of 6 treatments with 6 repetitions. When evaluating the effect of the bacteria Serratia nematodiphila in the treatment with irrigation to 25% of water, it was observed that the average values ​​of the root length of the tomato seedlings was the one that suffered the most stimulus in the root growth when compared to the other irrigation levels. These results suggest that under conditions of greater water deficit the bacteria is able to mitigate drought by promoting root growth.